Variació morfofonològica. Variants morfològiques - Maria Rosa Lloret; Joaquim Viaplana (Caplletra: Revista Internacional de Filologia, 2015)
Morphological variation can be considered to take place in two levels: on a superficial level of phonetic nature and on a deep level of phonological nature. This study addresses the deep level of morphological variation, of morphological variation strictly speaking. It focuses on the variations of the morphological variables, that is to say, on the actual realizations of morphological variation. There are two kinds of morphological variations: of formal and of grammatical nature. Formal morphological variations are those with a phonological representations in which morphological variation is present. These are existing morphological variations. Grammatical morphological variations are those which determine several formal variations in the declention of words. These morphological variations not readily available, but that become available through the corresponding formal morphological variations. Both kinds of variations are analyzed in terms of typology and of class.